2018
DOI: 10.1089/acm.2016.0379
|View full text |Cite
|
Sign up to set email alerts
|

Spearmint Extract Improves Working Memory in Men and Women with Age-Associated Memory Impairment

Abstract: Objective: The purpose of this study was to investigate the effects of supplementation with a spearmint (Mentha spicata L.) extract, high in polyphenols including rosmarinic acid, on cognitive performance, sleep, and mood in individuals with age-associated memory impairment (AAMI).Design: Subjects with AAMI (N = 90; 67% female; age = 59.4 ± 0.6 years) were randomly assigned (n = 30/group) to consume 900, 600, or 0 mg/day (two capsules, once daily) spearmint extract for 90 days, in this double-blind, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(85 citation statements)
references
References 49 publications
1
82
0
Order By: Relevance
“…144 Conversely, an aqueous extract of spearmint containing polyphenols but none of the plant's substantial monoterpene content improved cognitive function in older adults. 145 Similarly, lemon balm, which has been shown to produce acute anxiolytic and cognitive effects, contains flavonoids as well as monoterpenoid aldehydes and glycosides. 146 Therefore, it appears that different classes of terpenes have distinct mechanisms of action that produce varying effects.…”
Section: Polyphenols and The Potential Interaction With Other Bioactimentioning
confidence: 99%
“…144 Conversely, an aqueous extract of spearmint containing polyphenols but none of the plant's substantial monoterpene content improved cognitive function in older adults. 145 Similarly, lemon balm, which has been shown to produce acute anxiolytic and cognitive effects, contains flavonoids as well as monoterpenoid aldehydes and glycosides. 146 Therefore, it appears that different classes of terpenes have distinct mechanisms of action that produce varying effects.…”
Section: Polyphenols and The Potential Interaction With Other Bioactimentioning
confidence: 99%
“…A recent randomised controlled trial addressed the therapeutic potential of a herbal extract of Maritime pine bark (pycnogenol) in Attention deficit hyperactivity disorder [107]. Herrlinger et al [108] demonstrated in their study that spearmint extract improved working and spatial memory in older patients with age-associated memory impairments. Patients who were administered spearmint extract (900 mg/day) reported improvement in their ability to fall asleep in comparison to placebo group [108].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Currently, only one controlled trial has investigated the brain function effects of Mentha species in humans. Here promising effects were observed on quality of working memory and spatial working memory as well as improved sleep onset and vigour, alertness and overall mood in a group of 50–70 years olds following 90 days supplementation with 600 mg and 900 mg of an aqueous extract of Mentha spicata (spearmint) that contained the phenolic constituents but not the terpene constituents of the plant material [ 34 ]. The current study extends this research by investigating the cognitive and mood effects of oral administration of mint essential oil comprised of the volatile terpene phytochemical constituents of a Mentha plant, in healthy, young humans.…”
Section: Introductionmentioning
confidence: 99%